Olefin-based polymer

By calculating an S value of 0.60 or more for olefinic polymers, the ease of molding is significantly improved, addressing the challenges of existing polymers and resulting in enhanced moldability and processing characteristics.

JP2025063565APending Publication Date: 2025-04-16SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023172889
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing olefin polymers require further improvements in ease of molding, as they can be challenging to form effectively.

Method used

The development of an olefinic polymer with an S value calculated by a specific formula of 0.60 or more, which enhances the polymer's moldability by optimizing molecular weight distribution and crystallization temperature.

Benefits of technology

The resulting olefinic polymer is easier to form, with improved moldability and processing characteristics, such as increased melt tension and reduced oligomer content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063565000001
    Figure 2025063565000001
  • Figure 2025063565000002
    Figure 2025063565000002
  • Figure 2025063565000003
    Figure 2025063565000003
Patent Text Reader

Abstract

To provide an olefin-based polymer which is relatively easy to mold.SOLUTION: There is provided an olefin-based polymer which has an S value calculated by the following expression (i) of 0.60 or more. (In the formula, when a molecular weight distribution curve is drawn by using a log value (log A) of the size (A) of a molecule obtained by gel transmission chromatography as the x-axis and the concentration fraction (dW / d log A) of the polymer corresponding to the log value as the y-axis and the first differential is obtained by the Savitzky-Golay method, one of the smallest values having the smallest x is defined as LAmin and one of the minimum values having the largest x is defined as LAmax. In addition, a point where y is largest in the range where x equals to or is more than the x value in LAmin and x equals to or is less than the x value in LAmax is defined as GA and the area of the molecular weight distribution curve is defined as T.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an olefin polymer. [Background technology]

[0002] 2. Description of the Related Art Olefin polymers have conventionally been used for food packaging materials, pharmaceutical packaging materials, electronic component packaging materials, surface protective materials, insulators and sheaths for electric wires and cables, and the like.

[0003] For example, Patent Document 1 describes an ethylene-α-olefin copolymer that has a melt flow rate, density, flow activation energy, molecular weight distribution, and hexane extractable amount each falling within a specific range, and that can be used as a food packaging material and has excellent moldability and low smoke generation during melt processing. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-106264 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the olefin polymer disclosed in the above Patent Document 1 is required to be further improved in terms of ease of processing.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an olefin polymer which is relatively easy to process. [Means for solving the problem]

[0007] The olefin polymer according to the present invention has an S value calculated by the following formula (i) of 0.60 or more.

number

[0008] According to the present invention, it is possible to provide an olefin polymer that is relatively easy to mold. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.

[0010] From the viewpoint of easy moldability, the olefin polymer according to this embodiment has an S value calculated by the following formula (i) of 0.60 or more, preferably 1.0 or more, and more preferably 1.4 or more. From the viewpoint of easy moldability, the olefin polymer has an S value of preferably 2.0 or less, more preferably 1.8 or less, and even more preferably 1.4 or less.

[0011]

number

[0012] In the above formula (i), a molecular weight distribution curve is drawn with the log value (log A) of the molecular size (A) obtained by gel permeation chromatography on the x-axis and the polymer concentration fraction (dW / d log A) corresponding to the log value on the y-axis, and the first differential curve is obtained by the Savitzky-Golay method. Among the minimum values, the one with the smallest x is LA min, and the one with the largest x is LA max. In addition, the point where y is maximum in the range where x is equal to or greater than the x value at LA min and equal to or less than the x value at LA max is GA, and the area of ​​the molecular weight distribution curve is T. The first differential curve preferably has two minimum values. If the first differential curve has less than two minimum values, S=0.

[0013] The S value can be increased, for example, by decreasing the partial pressure of the main monomer in the gas phase polymerization, and the S value can be decreased, for example, by increasing the partial pressure of the main monomer in the gas phase polymerization.

[0014] The S value can be calculated by the following method. First, a GPC chromatogram is obtained by the method described below. The baseline on the chromatogram is specified based on the description in ISO16014-1. The S value can be calculated by the following method using Python.

[0015] The first step is to download and install the Anaconda version for the corresponding model and configure the environment.

[0016] In the second step, change the title of the first column of the electronic data of the GPC chromatogram to "x" and the title of the second column to "y". Next, enter the logM value from the second line of the first column and the dwt / d(logM) value from the second line of the second column, and save it as a csv file ('data name.csv').

[0017] In the third step, enter and run the code shown below using Jupyter Notebook (Anaconda3).

[0018] #Loading modules import glob import pandas as pd from scipy import signal

[0019] #Enter Data df = pd.read_csv('data name.csv')

[0020] #Perform smoothing and differentiation delta = df["x"].iat[1] - df["x"].iat[0] df["dy"] = signal.savgol_filter(df["y"], round((0.3 / delta - 1) / 2) * 2 + 1, 1, deriv=1, delta=delta) df["ddy"] = signal.savgol_filter(df["y"], round((0.6 / delta - 1) / 2) * 2 + 1, 2, deriv=2, delta=delta)

[0021] #Calculating S value l_mins = [] idxmax = df["y"].astype("float64").idxmax() for i in range(len(df["ddy"]) - 1 - idxmax): if df.at[df.index[i + idxmax], "ddy"] < 0 and df.at[df.index[i + idxmax + 1], "ddy"] > 0: l_mins.append(i + idxmax) if len(l_mins) < 2: s = 0 else: first_l_min_idx = min(l_mins) first_l_min_x = df.at[df.index[first_l_min_idx], "x"] first_l_min_y = df.at[df.index[first_l_min_idx], "dy"] last_l_min_idx = max(l_mins) last_l_min_x = df.at[df.index[last_l_min_idx], "x"] last_l_min_y = df.at[df.index[last_l_min_idx], "dy"] partial_df = df.query("@first_l_min_idx < index < @last_l_min_idx") partial_max_idx = partial_df["dy"].idxmax() partial_max_x = df.at[df.index[partial_max_idx], "x"] partial_max_y = df.at[df.index[partial_max_idx], "dy"] s = (partial_max_y - first_l_min_y) / (partial_max_x - first_l_min_x) print(s)

[0022] From the viewpoint of easy molding, the crystallization temperature of the olefin polymer according to the present embodiment is preferably 99.0° C. or more and 105.0° C. or less, more preferably 100.0° C. or more and 104.0° C. or less, and even more preferably 101.0° C. or more and 103.0° C. or less. The crystallization temperature can be increased, for example, by decreasing the ratio of the comonomer to the main monomer during polymerization. The crystallization temperature can be decreased, for example, by increasing the ratio of the comonomer to the main monomer during polymerization.

[0023] The crystallization temperature can be measured by the following steps 1) to 3) using a differential scanning calorimeter (DSC Q100, manufactured by TA Instruments). The crystallization temperature can be determined as the exothermic peak of the heat flow curve observed in step 2). 1) Approximately 10 mg of sample was kept at 150°C for 5 minutes in a nitrogen atmosphere. 2) Cooling: Hold at 150℃~20℃ or 0℃ (5℃ / min) for 2 minutes 3) Temperature rise: 20℃ or 0℃ to 150℃ (5℃ / min)

[0024] In the olefin polymer according to the present embodiment, the ratio (Mz / Mw) of the Z-average molecular weight (Mz) to the weight-average molecular weight (Mw) measured by gel permeation chromatography is preferably 2.5 or more and 2.8 or less, more preferably 2.6 or more and 2.8 or less, and even more preferably 2.7 or more and 2.8 or less, from the viewpoint of easy molding.

[0025] In the olefin polymer according to this embodiment, the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured by gel permeation chromatography is preferably 3.4 or more and 4.0 or less, more preferably 3.5 or more and 3.9 or less, and even more preferably 3.6 or more and 3.8 or less, from the viewpoint of easy molding.

[0026] The weight average molecular weight (Mw), number average molecular weight (Mn), and Z average molecular weight (Mz) can be measured by gel permeation chromatography (GPC) under the following conditions.

[0027] (Measurement conditions) Equipment: HLC-8321GPC / HT (Tosoh Corporation) GPC column: TOSOH TSKgelGMHHR-H(S)HT 7.8 ID×300mm (Tosoh Corporation) x 3 Mobile phase: Orthodichlorobenzene (Wako Pure Chemical Industries, Ltd., special grade) with 0.1 w / V BHT added Flow rate: 1mL / min Column oven temperature: 140°C Detection: Refractive index detector (RID) RID cell temperature: 140℃ Sample solution injection volume: 300 μL Sample solution concentration: 5mg / mL GPC column calibration standard material: Prepare by dissolving the standard polystyrene manufactured by Tosoh Corporation in 5 mL of orthodichlorobenzene (same composition as the mobile phase) at room temperature in the amounts shown in Table 1.

[0028] [Table 1]

[0029] When the olefin-based polymer according to the present embodiment is a copolymer described below, the number of long chain branches (LCB) per 1000 carbon atoms in the copolymer (LCB / 1000C) is preferably 0.19 or more and 0.25 or less, more preferably 0.21 or more and 0.23 or less. LCB / 1000C can be increased, for example, by decreasing the partial pressure of the main monomer in the gas phase polymerization. LCB / 1000C can be decreased, for example, by increasing the partial pressure of the main monomer in the gas phase polymerization.

[0030] The LCB / 1000C can be determined by measuring the carbon nuclear magnetic resonance (13C-NMR) spectrum of the copolymer under the following measurement conditions.

[0031] (Measurement conditions) Equipment: Bruker AVANCE600 Measurement probe: 10mm cryoprobe Measurement solvent: 1,2-dichlorobenzene-d4 Measurement temperature: 135℃ Measurement method: Proton decoupling method Pulse width: 45 degrees Pulse repetition time: 4 seconds Window functions: negative exponential and Gaussian functions Accumulation count: 5000

[0032] (How to calculate the number of long chain branches (LCB)) In the 13C-NMR spectrum, the peak area of ​​the methine carbon to which a branch having 7 or more carbon atoms is bonded is defined as LCB, when the sum of the peak areas of all peaks having a peak top at 5 to 50 ppm is 1000. LCB is the number of branches having 7 or more carbon atoms per 1000 carbon atoms in the copolymer. Under the present measurement conditions, the peak area A near 38.2 ppm analyzed by the exponential function is used as the standard, and the area near 38.2 ppm in the analysis using the Gaussian function is defined as the peak area A, and the LCB can be obtained from the peak area of ​​a newly appearing peak having a peak top at around 38.22 to 38.27 ppm. In the processing using the Gaussian function, the LB (line broadening factor) is set to a value of -3 to -0.1. The peak area of ​​the peak is the signal area in the range from the chemical shift of the valley between the peak that is most highly magnetic among the peaks present in the range and the adjacent peak on the high magnetic field side of the peak to the chemical shift of the valley between the peak that is most highly magnetic among the peaks present in the range and the adjacent peak on the low magnetic field side of the peak.

[0033] When the olefin-based polymer according to the present embodiment is a copolymer described below, the number of short chain branches (SCB) per 1000 carbon atoms in the copolymer (SCB / 1000C) is preferably 18.8 or less, more preferably 5.0 or more and 18.8 or less, and even more preferably 10.0 or more and 18.8 or less. SCB / 1000C can be increased, for example, by increasing the ratio of the comonomer to the main monomer during polymerization. SCB / 1000C can also be decreased, for example, by decreasing the ratio of the comonomer to the main monomer during polymerization.

[0034] SCB / 1000C performs an exponential analysis of the carbon nuclear magnetic resonance (13C-NMR) spectrum measured by the above method, and when the sum of the peak areas of all peaks having their tops in the range of 5 to 50 ppm is taken as 1000, the peak area derived from the methine carbon bonded to a branch having 4 carbon atoms can be calculated as the amount of short chain branches.

[0035] When the olefin-based polymer according to the present embodiment is a copolymer described below, the number of tri-substituted unsaturated bonds in the copolymer is preferably 0.001 or more and 0.010 or less, more preferably 0.003 or more and 0.008 or less, and even more preferably 0.005 or more and 0.006 or less. The number of tri-substituted unsaturated bonds in the copolymer can be increased, for example, by increasing the ratio of comonomer to main monomer during polymerization. Also, the number of tri-substituted unsaturated bonds in the copolymer can be decreased, for example, by decreasing the ratio of comonomer to main monomer during polymerization.

[0036] The number of tri-substituted unsaturated bonds in the copolymer can be determined by measuring the proton nuclear magnetic resonance (1H-NMR) spectrum of the copolymer under the following measurement conditions.

[0037] (Measurement conditions) Equipment: Bruker AVANCE600 Measurement probe: 10mm cryoprobe Measurement solvent: 1,2-dichlorobenzene-d4 Measurement temperature: 135℃ Sample concentration: 60mg / mL Accumulation count: 64

[0038] (Method of calculating the number of tri-substituted unsaturated bonds) In the 1H-NMR spectrum, the total peak area of ​​all peaks having a peak top between 3.0 and −0.5 ppm is taken as 1000, and the peak area derived from tri-substituted unsaturated bonds can be calculated as the number of tri-substituted unsaturated bonds.

[0039] The intrinsic viscosity of the olefin polymer according to the present embodiment is preferably 1.19 dl / g or more, more preferably 1.19 dl / g or more and 1.80 dl / g or less, and even more preferably 1.19 dl / g or more and 1.60 dl / g or less, from the viewpoint of easy molding. The intrinsic viscosity can be increased, for example, by decreasing the ratio of hydrogen to the main monomer during polymerization. The intrinsic viscosity can be decreased, for example, by increasing the ratio of hydrogen to the main monomer during polymerization. The intrinsic viscosity can be measured at 135°C by dissolving the polymer in a tetralin solvent and using an Ubbelohde viscometer.

[0040] The characteristic relaxation time of the olefin polymer according to the present embodiment is preferably 10.2 sec or more, more preferably 10.2 sec or more and 18.0 sec or less, and even more preferably 10.2 sec or more and 16.0 sec or less. The characteristic relaxation time can be increased, for example, by decreasing the ratio of hydrogen to the main monomer during polymerization. The characteristic relaxation time can be decreased, for example, by increasing the ratio of hydrogen to the main monomer during polymerization.

[0041] The characteristic relaxation time can be determined by the following method. First, a viscoelasticity measuring device ARES-G2 (manufactured by TA Instruments) is used to measure melt complex viscosity-angular frequency curves at 130°C, 150°C, 170°C, and 190°C under the following measurement conditions. Next, a master curve of the melt complex viscosity-angular frequency curve at 190°C is created from the obtained melt complex viscosity-angular frequency curves using analysis software TRIOS ver.5.0.0 (manufactured by TA Instruments), and the characteristic relaxation time is determined by approximating the obtained master curve with the following formula. η = η0 / [1 + (τ × ω) n ] η: Melt complex viscosity (unit: Pa sec) ω: Angular frequency (unit: rad / sec) τ: characteristic relaxation time (unit: sec) η0: constant determined for each ethylene-α-olefin copolymer (unit: Pa sec) n: constant determined for each ethylene-α-olefin copolymer

[0042] (Measurement conditions) Geometry: Parallel plate Plate diameter: 25mm Plate spacing: 1.5~2mm Strain: 5% Angular frequency: 100~0.1rad / sec Measurement atmosphere: Nitrogen

[0043] The melt complex viscosity (η* 100 From the viewpoint of excellent extrusion load during extrusion molding, the melt complex viscosity (η* 100 From the viewpoint of facilitating molding, the viscosity is preferably 300 Pa·sec or more, more preferably 500 Pa·sec or more, and even more preferably 1000 Pa·sec or more.

[0044] The oligomer content of the olefin polymer according to this embodiment is preferably 1500 ppm or less, more preferably 1200 ppm or less, and even more preferably 800 ppm or less, from the viewpoint of improving the working environment and facilitating molding.

[0045] The amount of oligomers can be determined by the following method. First, oligomer components are extracted from about 1 g of polymer by ultrasonic extraction using 10 ml of THF solvent. The amount of oligomer components can be determined by GC. The measuring device and each measuring condition are as follows.

[0046] (Measurement conditions) GC measuring device: GC-2025 manufactured by Shimadzu Corporation Column: GL Sciences InertCap1 (film thickness 1.50μm, length 15m, inner diameter 0.53mm) Detector (FID) temperature: 310℃ Measurement column temperature: Hold at 100°C for 1 minute, then increase to 310°C at 10°C / min The sum of the detected peak areas of hydrocarbons having 12 to 18 carbon atoms in the obtained gas chromatogram chart is converted into the concentration (ppm) of hydrocarbons having 18 carbon atoms.

[0047] Examples of the olefin-based polymer include ethylene-based polymers and propylene-based polymers. The olefin-based polymer is preferably an ethylene-based polymer. The olefin-based polymer may be used alone or in combination of two or more kinds.

[0048] (Ethylene polymer) The ethylene-based polymer is a polymer containing more than 50% by mass of monomer units derived from ethylene, that is, an ethylene homopolymer or an ethylene-based copolymer containing more than 50% by mass of monomer units derived from ethylene. Examples of monomer units other than ethylene contained in the ethylene-based copolymer include monomer units derived from α-olefins having 3 to 20 carbon atoms. The ethylene-based polymers may be used alone or in combination of two or more kinds.

[0049] The ethylene-based polymer is preferably an ethylene-α-olefin copolymer obtained by copolymerizing ethylene with an α-olefin having 3 to 20 carbon atoms. Examples of the α-olefin having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 4-methyl-1-pentene, and 4-methyl-1-hexene, and preferably propylene, 1-butene, or 1-hexene. The above α-olefin having 3 to 20 carbon atoms may be used alone or in combination of two or more.

[0050] The ethylene-α-olefin copolymer may contain at least one α-olefin selected from the group consisting of propylene, butene, and hexene. Examples of such ethylene-α-olefin copolymers include ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-propylene-1-butene copolymers, and ethylene-1-butene-1-hexene copolymers, and are preferably ethylene-1-butene copolymers, ethylene-1-hexene copolymers, and ethylene-1-butene-1-hexene copolymers.

[0051] The content of monomer units based on ethylene in the ethylene-α-olefin copolymer is usually more than 50% by mass and not more than 99% by mass, based on the total mass (100% by mass) of the ethylene-α-olefin copolymer. The content of monomer units based on an α-olefin having 3 to 20 carbon atoms in the ethylene-α-olefin copolymer is usually 1% by mass or more and less than 50% by mass, based on the total mass (100% by mass) of the ethylene-α-olefin copolymer.

[0052] The ethylene polymer has a melt flow rate (MFR) measured under conditions of a temperature of 190° C. and a load of 2.16 kg of preferably 0.10 g / 10 min to 10.00 g / 10 min, more preferably 0.20 g / 10 min to 10.00 g / 10 min. The MFR is measured according to Method A specified in JIS K7210-1995.

[0053] The density of ethylene polymers is usually 870 kg / m 3 More than 960kg / m 3 From the viewpoint of increasing the mechanical strength of the molded body, the density is preferably 940 kg / m 3 More preferably, it is 930 kg / m or less. 3 More preferably, it is 925 kg / m or less. 3 or less, and particularly preferably 920 kg / m 3 From the viewpoint of improving the heat resistance of the molded body, the density is preferably 880 kg / m 3More preferably, it is 890 kg / m or more. 3 The density is measured according to the method specified in JIS K7112-1980.

[0054] The ethylene homopolymer is preferably produced by a so-called "high pressure process." The production of the ethylene homopolymer by the "high pressure process" is generally carried out by polymerizing ethylene in the presence of a radical generator at a polymerization pressure of 140 to 300 MPa and a polymerization temperature of 200 to 300°C using a tank reactor or a tubular reactor.

[0055] Examples of methods for producing ethylene-α-olefin copolymers include a method of copolymerizing ethylene and an α-olefin in the presence of a polymerization catalyst that uses, as catalyst components, a support in which a cocatalyst component such as an organoaluminum compound or an organoaluminum oxy compound is supported on a particulate support, and a metallocene complex having a ligand having a structure in which two cyclopentadienyl-type anion skeletons are bonded via a bridging group such as an alkylene group or a silylene group.

[0056] In the polymerization catalyst using a carrier and a metallocene complex, an organoaluminum compound may be used as a catalyst component, and examples of the organoaluminum compound include triisobutylaluminum and tri-n-octylaluminum. In the system using an organoaluminum compound as a catalyst component, a polymer having a relatively high melt tension and easy to mold can be obtained. In the system not using an organoaluminum compound as a catalyst component, the amount of oligomers is relatively small, so that the working environment is excellent and a polymer that is easy to mold can be obtained.

[0057] Examples of the polymerization method include gas phase polymerization and slurry polymerization. Examples of the solvent used in the slurry polymerization include aliphatic hydrocarbon compounds such as butane, pentane, hexane, heptane, and octane, and aromatic hydrocarbon compounds such as benzene and toluene. The solvent used in the slurry polymerization is preferably butane. It is desirable not to remove the solvent used in the slurry polymerization after contacting the carrier with the metallocene complex.

[0058] Furthermore, a prepolymerization may be carried out before carrying out the main polymerization. The prepolymerized catalyst component is preferably used as a catalyst component or catalyst for the main polymerization.

[0059] The polymerization temperature is usually lower than the temperature at which the ethylene-α-olefin copolymer melts, and is preferably from 0° C. to 150° C., more preferably from 30° C. to 100° C., and even more preferably from 50° C. to 90° C. The polymerization time is usually from 1 hour to 20 hours.

[0060] (Propylene polymer) A propylene-based polymer is a polymer containing more than 50% by mass of a monomer unit derived from propylene. Examples of the propylene-based polymer include a propylene homopolymer, a random copolymer of propylene and a monomer other than propylene, and a heterophasic propylene polymer material. The propylene-based polymer may be used alone or in combination of two or more kinds.

[0061] The propylene homopolymer can be produced, for example, by carrying out a polymerization step of polymerizing propylene using a polymerization catalyst.

[0062] Examples of the polymerization catalyst include Ziegler type catalysts; Ziegler-Natta type catalysts; catalysts containing a compound of a transition metal of Group 4 of the periodic table having a cyclopentadienyl ring and an alkylaluminoxane; catalysts containing a compound of a transition metal of Group 4 of the periodic table having a cyclopentadienyl ring, a compound that reacts with the transition metal compound to form an ionic complex, and an organoaluminum compound; and catalysts modified by supporting a catalyst component (a compound of a transition metal of Group 4 of the periodic table having a cyclopentadienyl ring, a compound that forms an ionic complex, an organoaluminum compound, etc.) on inorganic particles (silica, clay minerals, etc.).

[0063] Examples of the polymerization catalyst include catalysts described in JP-A-61-218606, JP-A-5-194685, JP-A-7-216017, JP-A-9-316147, JP-A-10-212319, JP-A-2004-182981, JP-A-2010-168545, and JP-A-2011-246699.

[0064] Furthermore, a polymer obtained by prepolymerizing propylene in the presence of the above polymerization catalyst can also be used as the polymerization catalyst.

[0065] Examples of the polymerization method include bulk polymerization, solution polymerization, and gas phase polymerization. Here, bulk polymerization refers to a method in which polymerization is carried out using an olefin that is liquid at the polymerization temperature as a medium. Solution polymerization refers to a method in which polymerization is carried out in an inert hydrocarbon solvent such as propane, butane, isobutane, pentane, hexane, heptane, or octane. Gas phase polymerization refers to a method in which a gaseous monomer is used as a medium and the gaseous monomer is polymerized in the medium.

[0066] The polymerization method may be, for example, a batch method, a continuous method, or a combination thereof. The polymerization method may be a multi-stage method in which a plurality of polymerization reaction vessels are connected in series.

[0067] From the viewpoint of industrial and economical superiority, the polymerization method is preferably a continuous gas phase polymerization method or a bulk-gas phase polymerization method in which a bulk polymerization method and a gas phase polymerization method are carried out continuously.

[0068] Various conditions in the polymerization step (polymerization conditions such as polymerization temperature, polymerization pressure, monomer concentration, catalyst input amount, and polymerization time) may be appropriately determined depending on the molecular structure of the desired polymer.

[0069] In the method for producing a propylene homopolymer, other steps may be carried out before or after the polymerization step. For example, after the polymerization step, the polymer may be dried at a temperature equal to or lower than the melting temperature of the polymer, if necessary, in order to remove residual solvent contained in the polymer and ultralow molecular weight oligomers produced as by-products during production. Examples of the drying method include the methods described in JP-A-55-75410 and JP-A-2565753.

[0070] In the random copolymer of propylene and a monomer other than propylene, examples of the monomer unit other than propylene include ethylene and α-olefins having 4 to 12 carbon atoms. Examples of the α-olefins having 4 to 12 carbon atoms include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 4-methyl-1-pentene, and 4-methyl-1-hexene.

[0071] The random copolymer of propylene and a monomer other than propylene can be produced, for example, by polymerizing propylene and a monomer other than propylene according to the polymerization catalyst, polymerization method, polymerization system, and polymerization conditions that can be used in the production of the above-mentioned propylene homopolymer.

[0072] The heterophasic propylene polymerization material is a mixture containing polymer I containing 80% by mass or more of monomer units derived from propylene (wherein the total mass of polymer I is taken as 100% by mass), and polymer II containing monomer units derived from at least one α-olefin selected from the group consisting of ethylene and α-olefins having 4 to 12 carbon atoms, and monomer units derived from propylene.

[0073] In the heterophasic propylene polymerization material, examples of monomers other than propylene include ethylene and α-olefins having 4 or more carbon atoms. Examples of α-olefins having 4 or more carbon atoms include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 4-methyl-1-pentene, 4-methyl-1-hexene, etc.

[0074] The heterophasic propylene polymer material can be produced, for example, by carrying out a first polymerization step of polymerizing polymer I and a second polymerization step of polymerizing polymer II. These polymerization steps can be carried out according to the polymerization catalyst, polymerization method, polymerization scheme, and polymerization conditions that can be used in the production of the above-mentioned propylene homopolymer.

[0075] The polymer I may be, for example, a propylene homopolymer, or may contain a monomer unit derived from a monomer other than propylene. Examples of the polymer I containing a monomer unit derived from a monomer other than propylene include a propylene-ethylene copolymer, a propylene-1-butene copolymer, a propylene-1-hexene copolymer, a propylene-1-octene copolymer, a propylene-ethylene-1-butene copolymer, a propylene-ethylene-1-hexene copolymer, and a propylene-ethylene-1-octene copolymer.

[0076] The content of polymer I is preferably 50% by mass or more and 99% by mass or less, and more preferably 60% by mass or more and 95% by mass or less, based on the total mass (100% by mass) of the heterophasic propylene polymerization material.

[0077] Polymer II contains monomer units derived from at least one α-olefin selected from the group consisting of ethylene and α-olefins having 4 to 12 carbon atoms, and monomer units derived from propylene. Examples of the α-olefins having 4 to 12 carbon atoms include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 4-methyl-1-pentene, and 4-methyl-1-hexene.

[0078] The content of the polymer II is preferably 1% by mass or more and 50% by mass or less, and more preferably 5% by mass or more and 40% by mass or less, based on the total mass (100% by mass) of the heterophasic propylene polymerization material.

[0079] The propylene polymer has a melt flow rate (MFR) measured at a temperature of 230° C. and a load of 2.16 kg of preferably 0.1 g / 10 min or more, more preferably 1 g / 10 min or more and 300 g / 10 min or less. The MFR of the propylene polymer may be 5 g / 10 min or more and 100 g / 10 min or less, or 10 g / 10 min or more and 50 g / 10 min or less. The MFR is measured according to Method A specified in JIS K7210-1995.

[0080] The olefin-based polymer according to the present embodiment may be used as an olefin-based resin composition by adding additives as necessary. The olefin-based resin composition contains the olefin-based polymer according to the present embodiment in an amount of preferably 5% by mass to 95% by mass, more preferably 10% by mass to 90% by mass, and even more preferably 15% by mass to 85% by mass, based on the total amount of the olefin-based resin composition being 100% by mass.

[0081] Examples of the additives include organic peroxides, hindered amine light stabilizers, crosslinking assistants, ultraviolet absorbers, and silane coupling agents.

[0082] (1)Organic peroxide Organic peroxides are mainly used to crosslink olefin polymers. As the organic peroxide, an organic peroxide having a decomposition temperature (temperature at which the half-life is 1 hour) of 70 to 180°C, particularly 90 to 160°C, can be used. Examples of such organic peroxides include t-butylperoxyisopropyl carbonate, t-butylperoxy-2-ethylhexyl carbonate, t-butylperoxyacetate, t-butylperoxybenzoate, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3,1,1-di(t-butylperoxy)-3,4 ... ,3,5-trimethylcyclohexane, 1,1-di(t-butylperoxy)cyclohexane, methyl ethyl ketone peroxide, 2,5-dimethylhexyl-2,5-diperoxybenzoate, t-butyl hydroperoxide, p-menthane hydroperoxide, benzoyl peroxide, p-chlorobenzoyl peroxide, t-butyl peroxyisobutyrate, hydroxyheptyl peroxide, dicyclohexanone peroxide, etc.

[0083] The content of the organic peroxide is preferably 0.2 parts by mass or more and 5 parts by mass or less, more preferably 0.5 parts by mass or more and 3 parts by mass or less, and even more preferably 1 part by mass or more and 2 parts by mass or less, relative to 100 parts by mass of the olefin polymer according to the present embodiment. When the blending ratio of the organic peroxide is within the above range, the olefin polymer is sufficiently and uniformly crosslinked.

[0084] (2) Hindered amine light stabilizers The hindered amine light stabilizer captures radical species harmful to polymers and prevents new radicals from being generated. There are many types of hindered amine light stabilizers, ranging from low molecular weight compounds to high molecular weight compounds, and any conventionally known compounds can be used without any particular limitation.

[0085] Low molecular weight hindered amine light stabilizers include a mixture of 70% by weight of decanedioic acid bis(2,2,6,6-tetramethyl-1(octyloxy)-4-piperidinyl) ester, 1,1-dimethylethyl hydroperoxide, and octane (molecular weight 737) and 30% by weight of polypropylene; bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate (molecular weight 685); a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl-1,2,2,6,6-pentamethyl-4-piperidylsebacate (molecular weight 509); and bis(2,2,6,6-tetramethyl-4-piperidyl). tetrakis(2,2,6,6-tetramethyl-4-piperidyl)sebacate (molecular weight 481); tetrakis(1,2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butane tetracarboxylate (molecular weight 791); tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butane tetracarboxylate (molecular weight 847); a mixture of 2,2,6,6-tetramethyl-4-piperidyl-1,2,3,4-butane tetracarboxylate and tridecyl-1,2,3,4-butane tetracarboxylate (molecular weight 900); a mixture of 1,2,2,6,6-pentamethyl-4-piperidyl-1,2,3,4-butane tetracarboxylate and tridecyl-1,2,3,4-butane tetracarboxylate (molecular weight 900), and the like.

[0086] Examples of high molecular weight hindered amine light stabilizers include poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}] (molecular weight 2,000 to 3,100); polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol (molecular weight 3,100 to 4,000); N,N',N",N"'-tetrakis-(4,6-bis- A mixture of (butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10-diamine (molecular weight 2,286) and the above-mentioned polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol; polycondensation of dibutylamine-1,3,5-triazine-N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine (molecular weight 2,600 to 3,400), as well as 4-acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-acryloyloxy-1,2,2,6,6-pentamethylpiperidine, 4-acryloyloxy-1-ethyl-2,2,6,6-tetramethylpiperidine, 4-acryloyloxy-1-propyl-2,2,6,6-tetramethylpiperidine, 4-acryloyloxy-1-butyl-2,2,6,6-tetramethylpiperidine, 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine, 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine, Examples of the copolymer include copolymers of cyclic aminovinyl compounds and ethylene such as 1,2,2,6,6-pentamethylperidine, 4-methacryloyloxy-1-ethyl-2,2,6,6-tetramethylpiperidine, 4-methacryloyloxy-1-butyl-2,2,6,6-tetramethylpiperidine, 4-crotonoyloxy-2,2,6,6-tetramethylpiperidine, and 4-crotonoyloxy-1-propyl-2,2,6,6-tetramethylpiperidine. The above hindered amine light stabilizers may be used alone or in combination of two or more.

[0087] Among these, the hindered amine-based light stabilizer is preferably poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}] (molecular weight 2,000 to 3,100); a polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol (molecular weight 3,100 to 4,000); N,N',N",N"'-tetrakis-(4,6-bis-(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10-diamine ( A mixture of N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)butylamine and a polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol (molecular weight 2,286); a polycondensate of dibutylamine-1,3,5-triazine-N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine (molecular weight 2,600 to 3,400); or a copolymer of a cyclic aminovinyl compound and ethylene is used. This is because bleeding out of the hindered amine light stabilizer over time during use of the product is prevented. In addition, the hindered amine light stabilizer preferably has a melting point of 60°C or higher from the viewpoint of ease of preparation of the olefin resin composition.

[0088] The content of the hindered amine light stabilizer is preferably from 0.01 to 2.5 parts by mass, more preferably from 0.01 to 1.0 parts by mass, even more preferably from 0.01 to 0.5 parts by mass, particularly preferably from 0.01 to 0.2 parts by mass, and most preferably from 0.03 to 0.1 parts by mass, relative to 100 parts by mass of the olefin polymer according to this embodiment.

[0089] By making the content of the hindered amine-based light stabilizer 0.01 parts by mass or more, the stabilizing effect is sufficiently obtained, and by making it 2.5 parts by mass or less, discoloration of the resin caused by excessive addition of the hindered amine-based light stabilizer can be suppressed. In the olefin-based resin composition, the mass ratio of the organic peroxide to the hindered amine-based light stabilizer is preferably 1:0.01 to 1:10, more preferably 1:0.02 to 1:6.5. This makes it possible to significantly suppress yellowing of the resin.

[0090] (3) Crosslinking assistant The crosslinking aid is effective in promoting the crosslinking reaction and increasing the degree of crosslinking of the olefin-based polymer. Examples of the crosslinking aid include polyallyl compounds and poly(meth)acryloxy compounds. More specifically, examples of the crosslinking aid include polyallyl compounds such as triallyl isocyanurate, triallyl cyanurate, diallyl phthalate, diallyl fumarate, and diallyl maleate, poly(meth)acryloxy compounds such as ethylene glycol diacrylate, ethylene glycol dimethacrylate, and trimethylolpropane trimethacrylate, and divinylbenzene. The content of the crosslinking aid is more than 0 parts by mass and about 5 parts by mass or less with respect to 100 parts by mass of the olefin-based polymer according to this embodiment.

[0091] (4) Ultraviolet absorbers Examples of ultraviolet absorbing agents include various types of agents such as benzophenones, benzotriazoles, triazines, and salicylic acid esters.

[0092] Examples of benzophenone-based ultraviolet absorbers include 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-n-octadecyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone, 2-hydroxy-5-chlorobenzophenone, 2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and 2,2',4,4'-tetrahydroxybenzophenone.

[0093] Benzotriazole-based ultraviolet absorbers include hydroxyphenyl-substituted benzotriazole compounds, such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-t-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dimethylphenyl)benzotriazole, 2-(2-methyl-4-hydroxyphenyl)benzotriazole, 2-(2-hydroxy-3-methyl-5-t-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-t-amylphenyl)benzotriazole, and 2-(2-hydroxy-3,5-di-t-butylphenyl)benzotriazole. In addition, triazine-based ultraviolet absorbers include 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-(octyloxy)phenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-(hexyloxy)phenol, and the like. Examples of salicylic acid esters include phenyl salicylate, p-octylphenyl salicylate, etc. The content of the ultraviolet absorber is preferably 2.0 parts by mass or less, more preferably 0.05 parts by mass or more and 2.0 parts by mass or less, even more preferably 0.1 parts by mass or more and 1.0 parts by mass or less, particularly preferably 0.1 parts by mass or more and 0.5 parts by mass or less, and most preferably 0.2 parts by mass or more and 0.4 parts by mass or less, relative to 100 parts by mass of the olefin polymer according to this embodiment.

[0094] (5) Silane coupling agents Examples of the silane coupling agent include γ-chloropropyltrimethoxysilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyltrimethoxysilane, vinyl-tris-(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, etc. The silane coupling agent is preferably vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, or 3-acryloxypropyltrimethoxysilane. The content of the silane coupling agent is preferably more than 0 parts by mass and not more than 5 parts by mass, more preferably from 0.01 parts by mass to 4 parts by mass, even more preferably from 0.01 parts by mass to 2 parts by mass, and particularly preferably from 0.05 parts by mass to 1 part by mass, relative to 100 parts by mass of the olefin-based polymer according to this embodiment.

[0095] (6) Other added ingredients The olefin resin composition may contain other additives, such as antioxidants, crystal nucleating agents, clarifying agents, lubricants, colorants, dispersants, fillers, fluorescent brighteners, ultraviolet absorbers, and light stabilizers, as long as the additives do not significantly impair the object of the present invention.

[0096] The method of adding the additive to the olefin-based polymer according to the present embodiment may be a known melt-kneading method, such as a method of dry blending using a tumbler blender, a Henschel mixer, or the like, followed by melt-kneading using a single-screw extruder, a multi-screw extruder, or the like, or a method of melt-kneading using a kneader, a Banbury mixer, or the like.

[0097] The olefin-based polymer according to this embodiment, or an olefin-based resin composition obtained by adding an additive to the olefin-based polymer according to this embodiment, is used for, for example, sheets, containers, insulators such as electric wires and cables, sheaths, solar cell encapsulants, and the like.

[0098] A known molding method can be used to mold the olefin polymer according to the present embodiment or the olefin resin composition obtained by adding an additive to the olefin polymer according to the present embodiment into various molded articles. Examples of the known molding method include an extrusion molding method and a coating extrusion molding method for coating electric wires and pipes.

[0099] The present invention includes the following aspects. [1] An olefin polymer having an S value calculated by the following formula (i) of 0.60 or more.

number

[10] The olefin polymer according to any one of [1] to [9] above, wherein the olefin polymer is a copolymer, and the number of short-chain branches (SCB) per 1000 carbon atoms (SCB / 1000C) in the copolymer is 18.8 or less. [Examples]

[0100] Hereinafter, the present invention will be described more specifically with reference to examples, but the present invention is not limited to these examples. The measured values of each item in the detailed description of the invention, examples, and comparative examples were measured by the following methods.

[0101] [Physical Property Measurement Method] <S value, Mz / Mw, Mw / Mn> Using the GPC method, under the following conditions, the weight-average molecular weight (Mw), the number-average molecular weight (Mn), and the Z-average molecular weight (Mz) were measured to obtain a GPC chromatogram. The baseline on the chromatogram was defined based on the description of ISO16014-1.

[0102] (Measurement Conditions) Equipment: HLC-8321GPC / HT (Tosoh Corporation) GPC column: TOSOH TSKgelGMHHR-H(S)HT 7.8 ID×300mm (Tosoh Corporation) x 3 Mobile phase: Orthodichlorobenzene (Wako Pure Chemical Industries, special grade) with 0.1 w / V BHT added Flow rate: 1mL / min Column oven temperature: 140°C Detection: Refractive index detector (RID) RID cell temperature: 140℃ Sample solution injection volume: 300 μL Sample solution concentration: 5mg / mL GPC column calibration standard material: Prepare by dissolving the standard polystyrene manufactured by Tosoh in 5 mL of orthodichlorobenzene (same composition as the mobile phase) at room temperature in the amounts shown in Table 1 above.

[0103] The S value was calculated using Python as follows:

[0104] The first step is to download and install the Anaconda version for the corresponding model and configure the environment.

[0105] In the second step, change the title of the first column of the electronic data of the GPC chromatogram to "x" and the title of the second column to "y". Next, enter the logM value from the second line of the first column and the dwt / d(logM) value from the second line of the second column, and save it as a csv file ('data name.csv').

[0106] In the third step, enter and run the code shown below using Jupyter Notebook (Anaconda3).

[0107] #Loading modules import glob import pandas as pd from scipy import signal

[0108] #Enter Data df = pd.read_csv('data name.csv')

[0109] #Perform smoothing and differentiation delta = df["x"].iat[1] - df["x"].iat[0] df["dy"] = signal.savgol_filter(df["y"], round((0.3 / delta - 1) / 2) * 2 + 1, 1, deriv=1, delta=delta) df["ddy"] = signal.savgol_filter(df["y"], round((0.6 / delta - 1) / 2) * 2 + 1, 2, deriv=2, delta=delta)

[0110] #Calculating S value l_mins = [] idxmax = df["y"].astype("float64").idxmax() for i in range(len(df["ddy"]) - 1 - idxmax): if df.at[df.index[i + idxmax], "ddy"] < 0 and df.at[df.index[i + idxmax + 1], "ddy"] > 0: l_mins.append(i + idxmax) if len(l_mins) < 2: s = 0 else: first_l_min_idx = min(l_mins) first_l_min_x = df.at[df.index[first_l_min_idx], "x"] first_l_min_y = df.at[df.index[first_l_min_idx], "dy"] last_l_min_idx = max(l_mins) last_l_min_x = df.at[df.index[last_l_min_idx], "x"] last_l_min_y = df.at[df.index[last_l_min_idx], "dy"] partial_df = df.query("@first_l_min_idx < index < @last_l_min_idx") partial_max_idx = partial_df["dy"].idxmax() partial_max_x = df.at[df.index[partial_max_idx], "x"] partial_max_y = df.at[df.index[partial_max_idx], "dy"] s = (partial_max_y - first_l_min_y) / (partial_max_x - first_l_min_x) print(s)

[0111] <Melt tension (MT, unit: cN)> Using a melt tension tester manufactured by Toyo Seiki Seisakusho, the molten copolymer filled in a 9.55 mmφ barrel was extruded from an orifice with a diameter of 2.09 mmφ and a length of 8 mm at a piston descending speed of 5.5 mm / min at a temperature of 190°C. The extruded molten copolymer was wound up using a take-up roll with a diameter of 50 mmφ while increasing the rotation speed by 40 rpm / min per minute, and the tension was measured just before the molten copolymer broke. The maximum tension from the start of the take-up until the filament-like resin was broken was taken as the melt tension (MT). The higher the melt tension value, the higher the melt tension. Resins with high melt tension have excellent bubble stability during inflation molding and parison shape retention during hollow molding, and have small neck-in during T-die molding.

[0112] <Characteristic relaxation time (τ, unit: sec)> Using a viscoelasticity measuring device ARES-G2 (manufactured by TA Instruments), melt complex viscosity-angular frequency curves were measured at 130°C, 150°C, 170°C, and 190°C under the following measurement conditions. The samples used for the measurements were molded using a press molding machine manufactured by Shinto Metal Industries Co., Ltd. The sample was placed in a 2 mm thick mold, and a circular test piece with a diameter of 25 mm was prepared and used under the following conditions: preheating temperature 150°C, preheating time 5 minutes, heating temperature 150°C, heating time 2 minutes, heating pressure 5 MPa, cooling temperature 25°C, and cooling time 5 minutes.

[0113] Next, from the obtained melt complex viscosity-angular frequency curve, a master curve of the melt complex viscosity-angular frequency curve at 190°C was created using analysis software TRIOS ver.5.0.0 (manufactured by TA Instruments), and the characteristic relaxation time was calculated by approximating the obtained master curve with the following formula. η = η0 / [1 + (τ × ω) n ] η: Melt complex viscosity (unit: Pa sec) ω: Angular frequency (unit: rad / sec) τ: characteristic relaxation time (unit: sec) η0: constant determined for each ethylene-α-olefin copolymer (unit: Pa sec) n: constant determined for each ethylene-α-olefin copolymer

[0114] (Measurement conditions) Geometry: Parallel plate Plate diameter: 25mm Plate spacing: 1.5~2mm Strain: 5% Angular frequency: 100~0.1rad / sec Measurement atmosphere: Nitrogen

[0115] <Melt complex viscosity (η* 100 (unit: Pa·sec) In the measurement of the characteristic relaxation time τ, the melt complex viscosity was measured at a temperature of 150° C. and an angular frequency of 100 rad / sec.

[0116] <Intrinsic viscosity ([η], unit: dl / g)> The polymer was dissolved in a tetralin solvent, and the viscosity was measured at 135° C. using an Ubbelohde viscometer.

[0117] <Number of long chain branches (LCB) per 1000 carbon atoms in the copolymer (LCB / 1000C)> The carbon nuclear magnetic resonance (13C-NMR) spectrum of the copolymer was measured under the following measurement conditions.

[0118] (Measurement conditions) Equipment: Bruker AVANCE600 Measurement probe: 10mm cryoprobe Measurement solvent: 1,2-dichlorobenzene-d4 Measurement temperature: 135℃ Measurement method: Proton decoupling method Pulse width: 45 degrees Pulse repetition time: 4 seconds Window functions: negative exponential and Gaussian functions Accumulation count: 5000

[0119] (How to calculate the number of long chain branches (LCB)) In the 13C-NMR spectrum, the peak area of ​​the methine carbon to which a branch having 7 or more carbon atoms is bonded is defined as LCB, when the sum of the peak areas of all peaks having a peak top at 5 to 50 ppm is set to 1000. LCB is the number of branches having 7 or more carbon atoms per 1000 carbon atoms in the copolymer. In this measurement condition, the peak area A near 38.2 ppm analyzed by the exponential function was used as the standard, and the area near 38.2 ppm was further defined as the peak area A in the analysis using the Gaussian function, and the LCB was obtained from the peak area of ​​a newly appearing peak having a peak top at around 38.22 to 38.27 ppm. In the processing using the Gaussian function, the LB (line broadening factor) was set to a value of -3 to -0.1. The peak area of ​​the peak is the area of ​​the signal in the range from the chemical shift of the valley between the peak that is on the highest magnetic field side among the peaks present in the range and the peak adjacent to the highest magnetic field side of the peak to the chemical shift of the valley between the peak that is on the lowest magnetic field side among the peaks present in the range and the peak adjacent to the highest magnetic field side of the peak. Note that, under these measurement conditions, the peak top position of the peak derived from the methine carbon bonded to the hexyl branch in the measurement of the ethylene-1-octene copolymer was 38.21 ppm.

[0120] <Number of short chain branches (SCB) per 1000 carbon atoms in the copolymer (SCB / 1000C)> In the carbon nuclear magnetic resonance (13C-NMR) spectrum measured by the above method, analysis was performed using an exponential function, and the amount of short chain branches was calculated as the peak area derived from methine carbon bonded to a branch having four carbon atoms when the sum of the peak areas of all peaks having peak tops at 5 to 50 ppm was set to 1000. Under these measurement conditions, it was calculated from the sum of the areas of the peaks at 13.8 to 14.0 ppm and 14.0 to 14.2 ppm.

[0121] <Number of tri-substituted unsaturated bonds in copolymer ( / 1000C)> The proton nuclear magnetic resonance (1H-NMR) spectrum of the copolymer was measured under the following measurement conditions.

[0122] (Measurement conditions) Equipment: Bruker AVANCE600 Measurement probe: 10mm cryoprobe Measurement solvent: 1,2-dichlorobenzene-d4 Measurement temperature: 135℃ Sample concentration: 60mg / mL Accumulation count: 64

[0123] (Method of calculating the number of tri-substituted unsaturated bonds) In the 1H-NMR spectrum, the peak area derived from the tri-substituted unsaturated bond was calculated as the number of tri-substituted unsaturated bonds when the sum of the peak areas of all peaks having a peak top at 3.0 to -0.5 ppm was set to 1000. As the peak area derived from the tri-substituted unsaturated bond, the area of ​​the peak from 5.15 to 5.32 ppm was used under the measurement conditions.

[0124] <Oligomer amount (ΣCn; n = 12-18, unit: ppm)> Oligomer components were extracted from approximately 1 g of ethylene-α-olefin copolymer by ultrasonic extraction using 10 ml of THF solvent. The amount of oligomer components was determined by GC. The measurement device and each measurement condition are as follows.

[0125] (Measurement conditions) GC measuring device: GC-2025 manufactured by Shimadzu Corporation Column: GL Sciences InertCap1 (film thickness 1.50μm, length 15m, inner diameter 0.53mm) Detector (FID) temperature: 310℃ Measurement column temperature: Hold at 100°C for 1 minute, then increase to 310°C at 10°C / min The sum of the peak areas detected for hydrocarbons having 12 to 18 carbon atoms in the obtained gas chromatogram chart was converted into the concentration (ppm) of hydrocarbons having 18 carbon atoms.

[0126] <Crystallization temperature (Tc, unit: °C)> Measurements were performed using a differential scanning calorimeter (DSC Q100, manufactured by TA Instruments) according to the following steps 1) to 3). The crystallization temperature was determined as the exothermic peak of the heat flow curve observed during step 2). 1) Approximately 10 mg of sample was kept in a nitrogen atmosphere at 150°C for 5 minutes. 2) Cooling: Hold at 150℃~20℃ or 0℃ (5℃ / min) for 2 minutes 3) Temperature rise: 20℃ or 0℃ to 150℃ (5℃ / min) (Note that in Examples 1 and 2 and Comparative Examples 1 and 2, the lower limit temperature was set to 20° C., and in Examples 3 and 4 and Comparative Examples 3 and 4, the lower limit temperature was set to 0° C.)

[0127] Example 1 (1) Prepolymerization After drying under reduced pressure, the inside of a 3-liter autoclave equipped with a stirrer, which had been replaced with argon, was returned to normal pressure, 10.19 g of silica-supported methylaluminoxane carrier (manufactured by Lake Materials) was added, and the inside of the autoclave was evacuated. 288 g of butane was charged, and the temperature inside the system was raised to 70°C, after which 230 mg of dichloro[[(1,2,3,3a,7a-η)-1H-inden-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadiene-1-ylidene]]zirconium and 10 mL of hexane were added and stirred for 1 hour. Then, 1.0 mL of a hexane solution of triisobutylaluminum with a triisobutylaluminum concentration of 1 mmol / mL was added and stirred for 10 minutes. Then, polymerization was carried out for 150 minutes at 40° C. while continuously feeding an ethylene / hydrogen mixed gas (hydrogen=0.22 mol %) at a rate of 1 g / min. Then, butane, ethylene, and hydrogen were purged to obtain 162.1 g of a prepolymer.

[0128] (2) Polymerization After drying under reduced pressure, the inside of a 3-liter autoclave equipped with a stirrer, which had been replaced with argon, was evacuated, hydrogen was added so that its partial pressure was 0.015 MPa, 60 mL of 1-hexene and 681 g of butane were charged, and the temperature in the system was raised to 70°C, after which ethylene was introduced so that its partial pressure was 0.8 MPa, and the inside of the system was stabilized. 1.0 mL of a hexane solution of Pluronic L-61 (manufactured by Aldrich) with a concentration of 1.3 mg / mL and 1.0 mL of a hexane solution of triisobutylaluminum with a concentration of 1 mmol / mL were added thereto. Then, 316 mg of the prepolymer prepared in Example 1 (1) above was added. Polymerization was carried out at 70°C for 120 minutes while continuously feeding an ethylene / hydrogen mixed gas (hydrogen = 0.15 mol%) so as to maintain the total pressure and the hydrogen concentration in the gas constant during polymerization. Then, butane, ethylene and hydrogen were purged to obtain 111.2 g of an ethylene-1-hexene copolymer. The physical properties of the obtained ethylene-α-olefin copolymer are shown in Table 1.

[0129] Example 2 (1) Prepolymerization After drying under reduced pressure, the inside of a 3-liter autoclave equipped with a stirrer, which had been replaced with argon, was returned to normal pressure, 31 mg of surfactant-containing particles produced in the same manner as in Example 1(1) described in Japanese Patent No. 6295506, and 10.15 g of silica-supported methylaluminoxane carrier (manufactured by Lake Materials) were added, and the inside of the autoclave was evacuated. 288 g of butane was charged, and the temperature inside the system was raised to 70°C, after which 242 mg of dichloro[[(1,2,3,3a,7a-η)-1H-inden-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadiene-1-ylidene]]zirconium and 10 mL of hexane were added and stirred for 1 hour. Then, 1.0 mL of a hexane solution of triisobutylaluminum with a triisobutylaluminum concentration of 1 mmol / mL was added and stirred for 10 minutes. Then, polymerization was carried out at 40°C for 150 minutes while continuously feeding an ethylene / hydrogen mixed gas (hydrogen=0.20 mol%) at a rate of 1 g / min. Then, butane, ethylene and hydrogen were purged to obtain 156.3 g of a prepolymer.

[0130] (2) Polymerization The polymerization was carried out under the same conditions as in Example 1(2) above, except that 326 mg of the prepolymer prepared in Example 2(1) above was used and an ethylene / hydrogen mixed gas (hydrogen=0.17 mol%) was continuously supplied during polymerization, to obtain 144 g of an ethylene-1-hexene copolymer.

[0131] Example 3 (1) Prepolymerization In a reactor with a stirrer and an internal volume of 210 L, which had been previously replaced with nitrogen, 30 L of butane was added at room temperature, followed by 0.60 kg of silica-supported methylaluminoxane carrier (manufactured by Lake Materials). The temperature inside the reactor was then raised to 40°C, and 30.8 mmol of dichloro[[(1,2,3,3a,7a-η)-1H-inden-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadiene-1-ylidene]]zirconium was added and stirred for 1 hour. Then, ethylene was supplied at a rate of 2.0 kg / h per 1 kg of carrier component, and hydrogen was supplied at a rate of 2.3 L / h per 1 kg of carrier component (calculated at room temperature and normal pressure), and preliminary polymerization was carried out for a total of 9.8 hours. After the polymerization was completed, the temperature was maintained at 40°C and the reactor was kept on standby until the pressure inside the reactor dropped to 0.45 MPaG. The reactor pressure was then reduced to 0.4 MPaG, and the slurry-like prepolymerized catalyst component was transferred to a dryer and dried under nitrogen flow to obtain a prepolymerized catalyst component. The amount of ethylene polymer in the prepolymerized catalyst component was 16.1 g per 1 g of the monomer component.

[0132] (2) Gas-phase polymerization Ethylene and 1-hexene were copolymerized using a continuous fluidized bed gas phase polymerization reactor. The polymerization reaction temperature (Tr) was 89°C, the polymerization reaction pressure was 2.0 MPaG, the average residence time was 3.9 h, and the gas superficial velocity was 30 cm / s. The hydrogen concentration and 1-hexene concentration in the gas phase were maintained at 0.0025 mol and 0.0111 mol per 1 mol of ethylene, respectively, and triisobutylaluminum was supplied at a rate of 6.9 mmol / h, and Amito 102 (Kao Corporation) was supplied at a rate of 15.5 wtppm relative to the polyethylene produced. The prepolymerization catalyst component obtained in Example 3(1) above was supplied to the reactor in an amount such that the production rate of the produced polyethylene (LLDPE) was 20.8 kg / h.

[0133] Example 4 (1) Gas-phase polymerization The polymerization reaction was carried out under the same conditions as in Example 3(2) above, except that the polymerization reaction temperature was changed to 86°C, the average residence time to 3.8 hours, the gas superficial velocity to 40 cm / s, the hydrogen concentration and 1-hexene concentration in the gas phase were maintained at 0.0054 mol and 0.0165 mol per mol of ethylene, respectively, triisobutylaluminum was supplied at a rate of 8.6 mmol / h, Amit 102 was not supplied, and the production rate of polyethylene produced was 21.0 kg / h.

[0134] Comparative Example 1 (1) Preparation of supported catalyst In a three-neck flask with a capacity of 100 mL and previously purged with nitrogen, 5.09 g of silica-supported methylaluminoxane carrier (manufactured by Lake Materials), 50 mL of hexane, and 56.8 mg of dichloro[[(1,2,3,3a,7a-η)-1H-inden-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadiene-1-ylidene]]zirconium were added and stirred at room temperature for 1 hour. After that, the reactant was left to stand, the supernatant was removed, and the solid was washed with 50 mL of hexane. The washed solid was dried under vacuum to obtain 5.12 g of supported catalyst.

[0135] (2) Polymerization The same procedure as in Example 1(2) was repeated except that 32 mg of the supported catalyst prepared in Comparative Example 1(1) was used instead of the prepolymer and an ethylene / hydrogen mixed gas (hydrogen=0.23 mol%) was continuously supplied during polymerization, to obtain 106 g of an ethylene-1-hexene copolymer.

[0136] Comparative Example 2 (1) Preparation of solid catalyst component A solid catalyst component was prepared in the same manner as in the preparation of component (A) in Examples 1(1) and (2) described in JP 2009-79180 A. Elemental analysis revealed that Zn was 11% by mass and F was 6.0% by mass.

[0137] (2) Prepolymerization 3.95 ml of butane heated to about 60°C was added to a reactor equipped with a stirrer that had been previously purged with nitrogen. 3 After that, 6.0 mol of racemic ethylene bis(1-indenyl)zirconium diphenoxide was added and stirred for 2 hours. After the system was stabilized, 5 kg of ethylene and 5 liters of hydrogen (room temperature and pressure) were added to the reactor, and 60.1 kg of the above solid catalyst component and 35.0 L of a solution in which triisobutylaluminum was diluted to 20 wt % with n-hexane were added to the reactor to start preliminary polymerization. Ethylene and hydrogen (room temperature and pressure) were fed to the reactor at 60 kg / hr and 30 liters / hr, respectively, for 30 minutes, and then the temperature was raised to 50°C, and ethylene and hydrogen (room temperature and pressure) were fed at 180 kg / hr and 0.54 m 3 / hr. Prepolymerization was carried out for a total of 13.7 hours. After completion of the prepolymerization, the pressure inside the reactor was purged to 0.3 MPaG, and the slurry-like prepolymerized catalyst was transferred to a dryer and dried under nitrogen flow to obtain a prepolymerized catalyst component containing 40.2 g of polyethylene per 1 g of the solid catalyst component.

[0138] (3) Polymerization After drying under reduced pressure, the inside of a 3-liter autoclave equipped with a stirrer, which had been replaced with argon, was evacuated, hydrogen was added so that its partial pressure was 0.041 MPa, 160 mL of 1-hexene and 591 g of butane were charged, and the temperature in the system was raised to 70°C, after which ethylene was introduced so that its partial pressure was 1.6 MPa, and the inside of the system was stabilized. 1.0 mL of a hexane solution of triisobutylaluminum having a triisobutylaluminum concentration of 1 mmol / mL and 2.0 mL of a hexane solution of triethylaluminum having a triethylaluminum concentration of 0.1 mol / L were added thereto. Then, 426 mg of the prepolymer prepared in the above Comparative Example 2(1) was added. During the polymerization, ethylene / hydrogen mixed gas (hydrogen=0.43 mol%) was continuously fed so that the total pressure and the hydrogen concentration in the gas were kept constant, while polymerization was performed at 70°C for 180 minutes. Then, butane, ethylene and hydrogen were purged to obtain 87.4 g of an ethylene-1-hexene copolymer.

[0139] Comparative Example 3 (1) Preparation of solid catalyst component A solid catalyst component was prepared in the same manner as in Comparative Example 2(1). Elemental analysis revealed that Zn was 11% by mass and F was 5.9% by mass.

[0140] (2) Prepolymerization In a reactor equipped with a stirrer that had been previously purged with nitrogen, 4.15 m of butane heated to about 60°C was added. 3 After that, 6.0 mol of racemic ethylene bis(1-indenyl)zirconium diphenoxide was added and stirred for 2 hours. After the system was stabilized, 5 kg of ethylene and 5 liters of hydrogen (room temperature and pressure) were added to the reactor, and 60.4 kg of the above solid catalyst component and 35.1 L of a solution of triisobutylaluminum diluted to 20 wt % with n-hexane were added to the reactor to start preliminary polymerization. Ethylene and hydrogen (room temperature and pressure) were fed to the reactor at 60 kg / hr and 30 liters / hr, respectively, for 30 minutes, and then the temperature was raised to 50°C, and ethylene and hydrogen (room temperature and pressure) were fed at 174 kg / hr and 0.52 m, respectively. 3 / hr. Prepolymerization was carried out for a total of 14.2 hours. After completion of the prepolymerization, the pressure inside the reactor was purged to 0.3 MPaG, and the slurry-like prepolymerized catalyst was transferred to a dryer and dried under nitrogen flow to obtain a prepolymerized catalyst component containing 41.8 g of polyethylene per 1 g of the solid catalyst component.

[0141] (3) Gas-phase polymerization Ethylene and 1-hexene were copolymerized using a continuous fluidized bed gas phase polymerization reactor. The polymerization reaction temperature (Tr) was 82°C, the polymerization reaction pressure was 2.0 MPaG, the average residence time was 3.7 h, and the gas superficial velocity was 42 cm / s. The hydrogen concentration and 1-hexene concentration in the gas phase were maintained at 0.0127 mol and 0.0167 mol per 1 mol of ethylene, respectively, and triisobutylaluminum was supplied at a rate of 8.7 mmol / h and triethylamine was supplied at a rate of 0.27 mmol / h. The prepolymerization catalyst component obtained in Example 3(1) above was supplied to the reactor in an amount such that the production rate of the resulting polyethylene (LLDPE) was 22.0 kg / h.

[0142] Comparative Example 4 (1) Gas-phase polymerization The same conditions as those in Comparative Example 3(3) were used, except that the reaction temperature was changed to 81°C, the average residence time was changed to 3.8 h, the hydrogen concentration and 1-hexene concentration in the gas phase were maintained at 0.0184 mol and 0.0170 mol per mol of ethylene, respectively, and the production rate of the produced polyethylene (LLDPE) was changed to 21.3 kg / h.

[0143] [Table 2]

[0144] As can be seen from the results in Table 2, the ethylene-1-hexene copolymers of Examples 1 and 2, which satisfy all the constituent requirements of the present invention, have a relatively high melt tension and are therefore easy to mold. Also, the ethylene-1-hexene copolymers of Examples 3 and 4, which satisfy all the constituent requirements of the present invention, have a relatively small amount of oligomers and are therefore excellent in the working environment and easy to mold.

Claims

1. An olefin polymer having an S value calculated by the following formula (i) of 0.60 or more. [0010] (In the formula, a molecular weight distribution curve is drawn with the log value (log A) of the molecular size (A) obtained by gel permeation chromatography on the x-axis and the polymer concentration fraction (dW / d log A) corresponding to the log value on the y-axis, and the first differential curve is determined by the Savitzky-Golay method. Among the minimum values, the one with the smallest x is designated as LA min, and the one with the largest x is designated as LA max. Furthermore, the point at which y is maximum in the range where x is equal to or greater than the x value at LA min and equal to or less than the x value at LA max is designated as GA, and the area of ​​the molecular weight distribution curve is designated as T.)

2. The olefin polymer according to claim 1 , wherein the S value is 2.0 or less.

3. The olefin polymer according to claim 1 or 2, which has a crystallization temperature of 99.0°C or higher and 105.0°C or lower.

4. The olefin-based polymer according to claim 1 or 2, wherein the olefin-based polymer is a copolymer, and the number of long chain branches (LCBs) per 1000 carbon atoms in the copolymer (LCB / 1000C) is 0.19 or more and 0.25 or less.

5. 3. The olefin polymer according to claim 1, wherein the ratio (Mz / Mw) of Z-average molecular weight (Mz) to weight-average molecular weight (Mw) measured by gel permeation chromatography is 2.5 or more and 2.8 or less.

6. 3. The olefin polymer according to claim 1, wherein the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured by gel permeation chromatography is 3.4 or more and 4.0 or less.

7. 3. The olefin polymer according to claim 1, which is a copolymer having a number of tri-substituted unsaturated bonds of 0.001 or more and 0.010 or less.

8. 3. The olefin polymer according to claim 1, having an intrinsic viscosity of 1.19 dl / g or more.

9. 3. The olefin polymer according to claim 1, which has a characteristic relaxation time of 10.2 sec or more.

10. The olefin-based polymer according to claim 1 or 2, wherein the olefin-based polymer is a copolymer, and the number of short chain branches (SCB) per 1000 carbon atoms (SCB / 1000C) in the copolymer is 18.8 or less.

Citation Information

Patent Citations

  • ETHYLENE-alpha-OLEFIN COPOLYMER AND FOOD PACKAGING MATERIAL

    JP2008106264A